Natural preservation strategies: The potential of bioactive compounds from fruit and vegetable waste to reduce postharvest losses - Konstantinos Papoutsis; Zahra Shams; Mahboobeh Yazdani; Faraz Muneer; Mahbubjon Rahmatov; Nikwan Shariatipour; Evelyn Elizabeth Villanueva-Gutierrez; Monalisa Sahoo (Food Chemistry: X)
The fruit and vegetable (F&V) waste generated postharvest has the potential of being used for the recovery of bioactive compounds that can be reintroduced into the supply chain to extend the postharvest quality of fresh produce. This review provides in-depth insights into the potential use of natural extracts derived from F&V waste to maintain the commercial and nutritional quality of fresh F&V. The mechanisms of action are comprehensively discussed. Application methods such as edible coatings, dipping solutions, and active packaging films are the main techniques used for the application of natural extracts. Future research integrating advanced -omics technologies is encouraged to unravel the molecular interactions of these bioactive compounds, facilitating the development of environmentally friendly, scalable postharvest treatments. Addressing regulatory challenges and ensuring industry adoption will be crucial in transitioning toward natural alternatives for food preservation, ultimately reducing postharvest losses and promoting sustainability in the fresh produce supply chain.